Two ornamental species of Cryptanthus (Bromeliaceae, Bromelioideae) on the brink of extinction: a new species and its congener from the 19th century - Leme, Elton M. C.; Fernandez, Eduardo P.; Fontana, André P.; Almeida, Pedro S. De; Forzza, Rafaela C. (Phytotaxa, 2026)
The authors describe and illustrate a new species of Cryptanthus, C. pataxoanus, found within the Monte Pascoal National and Historical Park, and present new data on its closest morphological relative, C. beuckeri, both endemic to the Atlantic Forest of the state of Bahia, Brazil, and assessed as Critically Endangered (CR). The new taxon represents one of the most ornamental discoveries in recent years due to its marbled foliage, with contrasting greenish-yellow and dark green colors, which is similar to C. beuckeri. The main differences between C. pataxoanus and its closest relative include leaf blades not petiolate or the basal ones sometimes subpetiolate, the much broader portion of the blades distinctly longer, the narrower sepals covered by brown-centered trichomes, and petals without glandulose trichomes. The discovery of the new species results from cooperative work with the Pataxó indigenous community living in Barra Velha and Barra Velha do Monte Pascoal Indigenous Lands, located within the boundaries of the Monte Pascoal National and Historical Park. It symbolizes the inexhaustible richness of the Brazilian biodiversity in general and the Atlantic Forest of southern Bahia in particular, despite its current coexistence with high levels of threat.